Lichen planus after COVID-19 vaccination: A report of two cases - Salman H Alotaibi; Ruaa Alharithy; Faisal A Alsharif; Norah Alkhayal (Wolters Kluwer Medknow Publications, 2022)
Lichen planus is a T-cell-mediated inflammatory disease that can be associated with preexposure to particular agents encompassing vaccines, viruses, and drugs. The origin of the disease is unknown and has varying clinical presentations, the recent manufactured COVID-19 vaccines have been linked with several cutaneous reactions that are similar to the cutaneous manifestations of COVID-19 virus infection, the majority of people developed cutaneous manifestations after the second dose of Pfizer vaccine, recent cases have been reported as a flare of a preexisting lichen planus following the administering of the Pfizer vaccine. We present a two interesting cases that developed a dermatological condition post Pfizer-BioNTech's COVID-19 vaccine. The first case is a 60-year-old man, with a past medical history of having lichen planus 15 years ago, that have been treated and controlled successfully with topical therapy, flared up following the administration of Pfizer-BioNTech's COVID-19 vaccine. The second case is a 57-year-old female with a past medical history of hypertension and hypothyroidism controlled. Develop the new onset of lichen planus after receiving the third dose of the COVID 19 vaccine. The lesions arise 3 weeks after the third dose.